The plastid ancestor originated among one of the major cyanobacterial lineages - Ochoa de Alda, Jesús A G; Esteban, Rocio; Diago Egaña, María Luz; Houmard, Jean (Nature Communications, 2018)
The primary endosymbiotic origin of chloroplasts is now well established but the identification of the present cyanobacteria most closely related to the plastid ancestor remains debated. We analyse the evolutionary trajectory of a subset of highly conserved cyanobacterial proteins (core) along the plastid lineage, those which were not lost after the endosymbiosis. We concatenate the sequences of 33 cyanobacterial core proteins that share a congruent evolutionary history, with their eukaryotic counterparts to reconstruct their phylogeny using sophisticated evolutionary models. We perform an independent reconstruction using concatenated 16S and 23S rRNA sequences. These complementary approaches converge to a plastid origin occurring during the divergence of one of the major cyanobacterial lineages that include N2-fixing filamentous cyanobacteria and species able to differentiate heterocysts.
Keywords: Scopus